Work Strategy for Village-Owned Enterprises (BUMDES) in Create Product Featured Villages in The District Strong Muara Enim Regency - Randi Randi; Yulasteriyani Yulasteriyani; Ardi Saputra; Mery Yanti; Ridhah Taqwa (LPPM Universitas PGRI Sumatera Barat, 2024)
This research focuses on the Work Strategy of Village-Owned Enterprises (BUMDes ) in Creating Village Superior Products in Kelekar District, Muara Enim Regency. The purpose of this study is to analyze the Work Strategy of Village-Owned Enterprises (BUMDes ) in Creating Village Superior Products in Kelekar District, Muara Enim Regency. The superior product of the village is one of the flagship programs of the Ministry of PDTT One Village One Product (OVOP). So, it is important to have a work strategy to overcome BUMDes ' problems in the development of the creative economy and the utilization of village potential. Work strategies that BUMDes must carry out. Through field studies and documents in the village, villagers can improve the village economy through BUMDes by developing the village's superior product business. The results of the research show that BUMDes carries out work strategies to build networks and various types of businesses. The method in this study is qualitative research.